PROFITABILITAS, KAPITALISASI, LIABILITAS, DAN PROBABILITAS KEBANGKRUTAN BANK Studi pada Industri Perbankan Swasta di Indonesia - Rosyadi, Imron (Universitas Muhammadiyah Surakarta, 2006)
The purpose of this research was to examines and evidence empirically the effects of profitability(NIITA and NIATTA), capitalization (TETA) and liability (CDTD) on the probability ofbankâs bankruptcy. The sample are taken from commercial banking listed in Jakarta stock exchange(JSE) in the period of 2001 to 2002. The Logistic regressions model is used to estimate the probabilityof companyâs bankruptcy. The result of this study show that factors: profitability (NIITA andNIATTA), capitalization (TETA) and liability (CDTD) have significant effect to the probability ofbankâs bankruptcy. Using analysis of logistic regression the research found that probability bank ofbankruptcy (dummy variable) is dependent variable and NIITA, NIATTA, TETA, and CDTDat variable independent.